A review of sludge pretreatment methods and co-digestion to boost biogas production and energy self-sufficiency in wastewater treatment plants. (April 2021) - Volschan Junior, Isaac; de Almeida, Ronei; Cammarota, Magali Christe
Graphical abstract: Highlights: Co-digestion of sludge with other waste can double methane production in digesters. Temperature phased anaerobic digestion increases methane production by 50 % on average. Biological pretreatment and co-digestion combine high efficiency and low energy input. These techniques can contribute to WWTPs' energy self-sufficiency. Abstract: Regardless of the water sanitation infrastructure and the degree of water pollution abatement that it could promote, the debate has intensified about the adaptation of sewage treatment objectives to concepts of circular economy and sustainability. This discussion includes understanding how to promote more efficient use of energy and inputs and the utilization of intermediate and final resources that can be generated in the liquid, solid, and gaseous phases throughout the wastewater treatment. Growing concerns over energy security, environmental impacts, and rising energy costs of wastewater treatment plants have made the anaerobic digestion process a viable technology to produce renewable energy. Therefore, biogas generated in anaerobic sewage treatment units and anaerobic sludge digestion has great potential. This work aims to review recent advances in technology to induce biogas generation in anaerobic digesters, including pretreatment methods (thermal, physical-chemical, and biological) and co-digestion with other organic residues. Mechanisms, advantages, drawbacks, technical and economic aspects are discussed. Among the strategies evaluated, biological pretreatment and co-digestion are more promising in terms of efficiency and costs. Nevertheless, these technologies should be carefully assessed from different perspectives to consolidate their full-scale application.